PENGGUNAAN TERAPI BERMAIN TERHADAP KECEMASAN SEBELUM PENCABUTAN GIGI SUSU ANAK USIA PRA SEKOLAH - Alfiyah Immawati; Siti Sulastri; Sutrisno Sutrisno (Journal of Oral Health Care, 2014)
The children and games are two of the thoughts which arenot able to be separated. Trough games they can handle thefeeling of ananxious and afraid. Generally the feeling of anxiousand afraid occur high before an exodontie decidui the tochildren in pre elementary school, especially in PuskesmasPakem there are four tenth children undergo the feeling ofanxious and afraid during the exodontie decidui. So it happensmoothly. Giving the game of therapy to them before havingthe first exodontie can reduce that feeling. This research is apre-experimental using design Pretest - posttest. Location ofresearch in dental poly Puskesmas Pakem. The method usedin this research is a method of random sampling and thesample was 30 respondens. Before given that therapy, theyare measured to response the feeling of anxious first throughan answer sheet observation which contains 14 items,Hamilton Anxiety Rating Scale( HARS). Then they are givento set up the puzzles in five minutes maximally. The next isthe measurement of the second response. The data was analyzedusing the Paired t test at the 0,000 significance. Theresults of the analyzing the use this therapy against the anxietybefore the exodontie decidui is <0,05 (p<0,05) significance.There are differences of the anxiety before and after beinggiven the therapy.